Probing Language Teachers’ Stroking and Credibility in Relation to Their Success in Class - Pishghadam, Reza; Karami, Maliheh (Alberta Journal of Educational Research, 2018)
Given the significance of teacher success in the adequacy of teaching and learning, the present study aims to examine the role of two factors, namely teacher stroking (teacher attention) and teacher credibility in relation to teacher success. To do so, a total of 301 English as a foreign language (EFL) learners completed three survey instruments: the Student Stroke Scale, the Source Credibility Scale, and the Characteristics of Successful Teachers Questionnaire. Using confirmatory factor analysis (CFA), first the construct validity of the Source Credibility Scale was substantiated, and then the associations among all three scales were examined. The results of CFA and correlation analyses revealed that teacher effectiveness correlated significantly and positively with both the components of stroke and that of teacher credibility. We conclude with a discussion of the results and implications for teaching and learning. Compte tenu de la signification de la réussite des enseignants dans l’efficacité de l’enseignement et de l’apprentissage, la présente étude a comme objectif d’examiner le rôle que jouent deux facteurs, l’encadrement personnalisé par l’enseignant et la crédibilité des enseignants. Nos données proviennent de trois outils de sondage (échelle d’encadrement personnalisé; échelle de crédibilité de la source; questionnaire sur les caractéristiques des enseignants efficaces) auprès de 301 étudiants d’anglais langue étrangère (ALE). Une analyse factorielle confirmatoire a établi la validité conceptuelle et les liens entre les trois échelles ont ensuite été étudiés. Les résultats de l’analyse factorielle confirmatoire et des analyses de corrélation ont révélé une corrélation significative et positive entre l’efficacité des enseignants d’une part et l’encadrement personnalisé et la crédibilité d’autre part. Nous concluons par une discussion des résultats et la présentation de leur impact sur l’enseignement et l’apprentissage.